Evolution of female urinary continence after physical therapy and associated factors - Prudencio, Caroline Baldini; De Aquino Nava, Guilherme Thomaz; Cardoso, Marco Aurélio [UNESP]; Marreto, Rafaela Bresciani [UNESP]; Sousa, Érica Almeida [UNESP]; Valenti, Vitor E. [UNESP]; Barbosa, Angélica Mércia Pascon (Springer Nature, 2014)
Background: Urinary incontinence (UI) is defined as any involuntary loss of urine that can influence the quality of life, personal hygiene and social interaction. The types of UI that most affect women are stress urinary incontinence, urge incontinence and mixed urinary incontinence. There are several risk factors that result in specific treatments. We aimed to investigate the evolution of female urinary continence after physical therapy intervention and its associated factors. Method. A retrospective cross-sectional study was conducted with 71 participants who were discharged from physiotherapy sector from August 2006 to April 2012 and met the inclusion criteria. Results: Among the studied variables, the number of sessions and completion of home pelvic floor exercises showed a significant association. The urinary continence appeared in 43.7% of the cases, and factors, performance of home exercises, and number of sessions showed a significant association. Conclusion: The number of sessions and completion of home pelvic floor exercises showed a significant relationship with each other. © 2014 Prudencio et al.; licensee BioMed Central Ltd.
Keywords: Patient outcome assessment; Urinary incontinence; Urogynecology; Women's health